Legal method essentials for Scots law - McFadzean, Dale; Irvine, Lynn Allardyce (Edinburgh law essentials., 2017)
Get started with using the library; find out what statutory interpretation and judicious precedent are; learn about finding and using case law and legislation; discover how to access and cite books, journals and other sources; take your study international with a guide to sources from Europe and further afield; and sail through your coursework and exams with handy tips for legal writing and research.